A pilot study on procedural sedation among adult patients at Emergency Department HUSM, Kelantan comparing fentanyl with midazolam versus fentanyl with propofol - Hashim, Ahmad (2006)
Introduction This is a pilot study looking at the safety and effectiveness of procedural sedation technique carried out at the Emergency Department (ED) HUSM Kelantan over a period of one year extending from December 2004 to December 2005. In other words, there were no study has been carried out before to compare the effectiveness and efficacy of using midazolam and propofol for any brief, intense procedures in ED setting. With this study, the standard drugs used and the measures during procedural sedation can be applied in all emergency departments. Objectives The objectives are: 1. to compare the safety and efficacy between a combination of fentanyl and propofol with fentanyl and midazolam; 2. to obsetVe outcomes in subjects. undergoing a procedure at the ED when they are under procedural sedation. These outcomes include the blood pressure, mean arterial pressure, respiratory rate, heart rate, oxygen saturation, end tidal carbon dioxide and duration to regain full consciousness after the procedural sedation. Methodology Fourty patients were needed for its significant evaluation in this study. They were randomly selected using the computer generated randotn permuted blocks of four patients. 20 patients were grouped together as A and the remaining 20 patients as group B. Drugs used were single blinded to prevent any biasness. Drug A represents proporfol while drug B represents midazolam. The procedures involved include, orthopaedic manipulation such as reduction of fractures, reduction of dislocated joints, abcess drainage, toilet and wound debridment, laceration wounds repaired and cardioversion. These subjects were monitored for their vital signs and end tidal carbon dioxide every ten minutes till the procedure is completed. The duration of recovery were documented when the subjects had completed the procedure until regaining a full consciousness or recovery. Patients were continued to be monitored at the observation ward before being discharged home or admitted to the respective ward. These findings were analysed using Mann-Whytney U statistical analysis. Result Majority of patients under study were represented by Malays and 75.6% were males. The youngest subject was 13 years old while the oldest was 78 years of age with the mean age of37.8 years. None of the patients developed any complication while under procedural sedation. Both propofol and mizadolam were found to be not significant (p value> 0.05) in outcomes as follow: 1) Blood pressure 2) Mean Arterial pressure 3) Heart rate 4) Respiratory Rate 5) Oxygen saturation 6) End tidal C02 This study also found that patients who received propofol (mean 29 ± 11.03) regained full consciousness at a much faster rate when compared to midazolam (mean 71.75 ± 60.63), p value< 0.001, better choice of drug to be used in the ED setting for procedural sedation. The recommended dose for propofol to be used for procedural sedation at the ED setting is lmglkg as a bolus dose followed by 0.5mglkg if required in a titrating dose while for midazolam the recommended dose is 0.1 mg/kg as a bolus dose followed by O.lmg/kg if needed in a titrating dose. Capnograph has proven to be a very sensitive instrument to detect early sign of hypoventilation and is strongly recommended to be used when procedural sedation is performed at the ED setting. Conclusion This pilot study has proved there were no difference between the studied drugs midazolam and propofol during procedural sedation. Instead, propofol has shown to be more efficacious and shortened the recovery time for patients to regain full consciousness. These two drugs can be used as procedura1 sedation agents in ED for various short intense painfu] procedures.